Distribución de especies de matorral en suelos ácidos y básicos de la Sierra de Grazalema, sur de España - Gallego Fernández, Juan Bautista (Anales del Jardín Botánico de Madrid, 2002)
The presence of Mediterranean shrubland woody species on acid or basic soils was studied at Grazalema Mountains. Transects were made at 137 sampling sites in the study área and 74 species were recognized. Phlomis purpurea. Cistus albidus. Quercus rotundifolia and Ulex baeticus were the most frequent species, being present at 70 % of the transects. Pistacia lentiscus. Rubia peregrina and Daphne gnidium were found in 50 % of the transects. From the total species recorded, 67 species were located on basic soils and 55 on acid soils; 19 species (25.7 %) were located only on basic soils and 7 species (9.5 %) only on acid soils; 21 species were significantly more frequent on basic soils, and 10 species on acid soils. The number of species per transect were significantly higher on basic soils (13.2 ± 3.8) than on acid soils (10.3 ± 3.7). Differences in species number are related to a higher number of species displaying a narrow distribution in the basic shrublands as well as due to species loss in the acid shrublands, as a consequence of geographic isolation and human disturbance.
Keywords: Betic ranges; Mediterranean shrubland; soil pH

Distribución de especies de matorral en suelos ácidos y básicos de la Sierra de Grazalema, sur de España - Gallego Fernández, Juan Bautista (Anales del Jardín Botánico de Madrid, 2002)
The presence of Mediterranean shrubland woody species on acid or basic soils was studied at Grazalema Mountains. Transects were made at 137 sampling sites in the study área and 74 species were recognized. Phlomis purpurea. Cistus albidus. Quercus rotundifolia and Ulex baeticus were the most frequent species, being present at 70 % of the transects. Pistacia lentiscus. Rubia peregrina and Daphne gnidium were found in 50 % of the transects. From the total species recorded, 67 species were located on basic soils and 55 on acid soils; 19 species (25.7 %) were located only on basic soils and 7 species (9.5 %) only on acid soils; 21 species were significantly more frequent on basic soils, and 10 species on acid soils. The number of species per transect were significantly higher on basic soils (13.2 ± 3.8) than on acid soils (10.3 ± 3.7). Differences in species number are related to a higher number of species displaying a narrow distribution in the basic shrublands as well as due to species loss in the acid shrublands, as a consequence of geographic isolation and human disturbance.
Keywords: Betic ranges; Mediterranean shrubland; soil pH